The first report of disease in a basking shark (Cetorhinus maximus) - Dagleish, Mark P; Baily, Johanna; Foster, Geoff; Reid, Robert J; Barley, Jason P (Journal of Comparative Pathology, 2010)
Few diseases have been reported in any species of shark and none in the basking shark (Cetorhinus maximus) despite the latter being the subject of targeted hunting for over two centuries. This is the first report to describe the clinical signs and gross and microscopical pathology in a diseased basking shark that was live-stranded on the east coast of Scotland. Pyogranulomatous meningoencephalitis was present together with multifocal, predominantly non-suppurative, myocarditis with myocyte necrosis, oedema and haemorrhage. Additionally, there was full thickness ulcerative and fibrinonecrotizing dermatitis with underlying granulomatous inflammation. The aetiology could not be determined, but the lesions were suggestive of an infectious process, possibly bacterial.